Effect of Warm Mix Asphalt (WMA) Antistripping Agent on Performance of Waste Engine Oil-Rejuvenated Asphalt Binders and Mixtures - Eltwati, Ahmed; Putra Jaya, Ramadhansyah; Azman, Mohamed; Euniza, Jusli; Al-Saffar, Zaid; Mohd Rosli, Hainin; Enieb, Mahmoud (MDPI, 2023)
Evaluating the performance of rejuvenated asphalt mixes is crucial for pavement design and construction, as using a rejuvenator not only boosts recycling and contributes to positive effects on the environment but also increases the sensitivity to rutting and moisture. This study was executed to evaluate the effect of a warm mix asphalt (WMA) antistripping agent, namely nano-ZycoTherm, on the moisture-induced damage and rutting potential of asphalt mixtures containing 30% and 60% aged (RAP) binder and rejuvenated with 12% waste engine oil (WEO). For this purpose, the rutting resistance of asphalt mixes in wet and dry conditions was examined utilizing a loaded wheel tracker. In addition, the impacts of moisture on the performance of the mixtures were evaluated using different experiments, such as modified Lottman (AASHTO T283), resilient modulus, dynamic creep, aggregate coating and wheel tracking tests. Fourier transform infrared (FTIR) spectroscopy and thermogravimetric (TG) analysis were performed to identify the functional groups, which would be significant in terms of moisture damage, and to assess the thermal stability of binder samples, respectively. The results revealed that the rejuvenation of aged binder with WEO increases the moisture susceptibility of the mixtures; however, the addition of ZycoTherm was found to enhance the moisture resistance of WEO-rejuvenated mixtures. Furthermore, the results indicated that the WEO-rejuvenated mixtures modified with ZycoTherm exhibited a better rutting resistance in a wet condition compared to that of WEO-rejuvenated and conventional HMA mixtures. However, the rejuvenated mixtures modified with ZycoTherm showed poorer rutting performance in a dry condition. In summary, the adoption of the WMA antistripping agent, RAP binder and WEO rejuvenation techniques demonstrated satisfactory outcomes in terms of rutting resistance and moisture susceptibility, and also, these techniques are much less expensive to implement.